Queer expectations: a genealogy of Jewish women's poetry - Weiman-Kelman, Zohar (SUNY Series in Contemporary Jewish Literature and Culture Ser, 2018)
Intro -- Contents -- Acknowledgments -- Introduction What to Expect When You're Not Expecting -- Chapter One Queer Lines: Adrienne Rich and Kadya Molodowsky -- Chapter Two Vanished Hellas and Hebraic Pain: Emma Lazarus and Anna Margolin -- Chapter Three Waiting in Vain: Leah Goldberg and Anna Margolin -- Chapter Four Heys Haunting: Poetics of Lesbian History -- Chapter Five Community across Discontinuity -- Chapter Six Translating Generations: Irena Klepfisz -- Coda Queering the Present of Jewish Literary History -- Notes -- Bibliography -- Index